Implementing ‘De KeLuVa’ Media Based on the Tri-N Approach to Improve Cognitive Learning Outcomes of Fourth Grade Elementary Students - Anisa Khayati Nur Kafah; Ita Handayani; Widyah Noviana; Weni Gurita Aedi (Universitas Veteran Bangun Nusantara, 2026)
Education plays an important role in developing students’ character, intellectual abilities, and problem-solving skills, particularly in mathematics education. However, mathematics learning in elementary schools is often dominated by teacher-centered instruction, resulting in low student engagement and cognitive learning outcomes. Therefore, this study aimed to analyze the implementation of De KeLuVa media based on the Tri-N approach (Niteni, Nirokke, and Nambahi) to improve fourth-grade students’ cognitive learning outcomes in mathematics, especially on the topic of perimeter and area of plane figures. This study employed Classroom Action Research (CAR) using the Kemmis and McTaggart cyclical model consisting of planning, acting, observing, and reflecting stages. The subjects of the study were 28 fourth-grade students of Mekarwangi Elementary School selected purposively based on their low mathematics learning achievement. Data were collected through cognitive achievement tests, classroom observations, and documentation. The research instruments were validated through expert judgment and content validity review. The results showed a significant improvement in students’ cognitive learning outcomes after the implementation of De KeLuVa media. The average score increased from 38.40 in the pre-cycle stage to 63.57 in Cycle I and reached 81.43 in Cycle II. In addition, students became more active, collaborative, and confident during mathematics learning activities. The findings indicate that the integration of De KeLuVa media and the Tri-N approach provides meaningful and deep learning experiences by encouraging students to observe, imitate, and modify mathematical problem-solving strategies. In conclusion, the implementation of De KeLuVa media based on the Tri-N approach effectively improved students’ cognitive learning outcomes in mathematics. This study implies that innovative and student-centered mathematics learning media can support deep learning processes and enhance elementary students’ conceptual understanding.